Respuesta :
[tex]a)\ A=0\\\\then\ Ax+By=C\Rightarrow By=C\to y=\frac{C}{B}\\\\picture\ \#1[/tex]
[tex]b)\ B=0\\\\then\ Ax+By=C\Rightarrow Ax=C\to x=\frac{C}{A}\\\\picture\ \#2[/tex]
[tex]c)\ C=0\\\\then\ Ax+By=C\Rightarrow Ax+By=0\to By=-Ax\to y=-\frac{A}{B}x\\\\picture\ \#3[/tex]
[tex]b)\ B=0\\\\then\ Ax+By=C\Rightarrow Ax=C\to x=\frac{C}{A}\\\\picture\ \#2[/tex]
[tex]c)\ C=0\\\\then\ Ax+By=C\Rightarrow Ax+By=0\to By=-Ax\to y=-\frac{A}{B}x\\\\picture\ \#3[/tex]
![Ver imagen Аноним](https://us-static.z-dn.net/files/d2a/aa1227f2085e1a08332667083880733d.png)
![Ver imagen Аноним](https://us-static.z-dn.net/files/df5/4bcfe081e85d75e47406d2cb3336eb5b.png)
![Ver imagen Аноним](https://us-static.z-dn.net/files/dbf/550b953096523f73afbd8b13f3f1761a.png)